The prevalence of bruxism and related factors in patients with multiple sclerosis: a comparative study - Odabas, Faruk Ömer; Uca, Ali Ulvi (Arquivos de Neuro-Psiquiatria, 2019)
Objective: To determine the prevalence of bruxism and related factors in patients with multiple sclerosis (MS).Methods: Diagnosed with relapsing-remitting MS under the 2010-revised McDonald diagnostic criteria, 182 patients without MS exacerbations during the previous three months were included in the patient group, and 145 healthy individuals made up the control group in the study. Demographic data of the participants in both groups were determined. In the patient and control groups, the diagnosis of definite bruxism was made using the International Classification of Sleep Disorders (Diagnosis and Coding Manual, Second Edition).Results: Bruxism was found in 29.7% (n = 54) of the patients and in 12.4% (n = 18) of the controls, and the difference was statistically significant (p < 0.001). Of all patients, the onset of bruxism was found in 70.4% (n = 38) after the diagnosis and in 29.6% (n = 169) prior to the diagnosis of MS. Compared with those without bruxism, the mean age (p = 0.031) and the score of the Expanded Disability Status Scale (p = 0.001) were also significantly higher among MS patients with bruxism. Between MS patients with and without bruxism, no significant differences were found in terms of sex, marital status, educational status, employment, cigarette smoking, total number of exacerbations, number of exacerbations within the previous year, and drugs used.Conclusions: The frequency of bruxism was found to be higher in the patients with MS than in the controls. Bruxism is associated with age and the Expanded Disability Status Scale score in MS patients.
Keywords: Bruxism; multiple sclerosis